WAYS TO IMPROVE THE PRACTICALITY OF USING TOURIST RESOURCES IN THE EFFECTIVE DEVELOPMENT OF TOURISM IN SAMARKAND REGIONS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores strategies to enhance the practical utilization of tourist resources in the Samarkand region of Uzbekistan to foster effective tourism development. By analyzing existing literature, employing a SWOT analysis, and gathering expert opinions, the study identifies key opportunities and challenges. The proposed methods focus on infrastructure improvement, community involvement, sustainable practices, and digital marketing to maximize the region's tourism potential. Results indicate that coordinated efforts in resource management and stakeholder collaboration can significantly boost tourism. The discussion highlights the importance of balancing economic growth with cultural and environmental preservation, offering practical suggestions for policymakers and tourism stakeholders.